Technology mapping – proposal of a method of technology analysis in foresight studies - Gudanowska, Alicja E. (Business: Theory and Practice, 2016)
The purpose of the article was to exhibit the technology mapping method as one of the methods which may be used in foresight research. Foresight studies was described in the context of technology as well as technology analysis. The main part of the article is the presentation of an original proposal of a technology mapping method enabling to diagnose the current state of technology. The execution of the method should allow to maximise the resources of knowledge on specific technologies. A list of technological knowledge base elements which might emerge as a result of the process was also described.